Kudaman. [anthology].
By the river Tabunganan is a spring, which is the abode of an evil spirit. Tuwan Putli, accompanied by her cousin Ambaynan, goes there to fish. As they are about to leave, Tuwan Putli sees a river lobster with golden pincers. Ambaynan waits for her, but Tuwan Putli disappears. There is blood in her fish basket. Ambaynan goes home and reports the incident.-- Source: https://www.kapitbisig.com/philippines/english-version-of-epics-mga-epiko-kudaman-of-palawan_1184.html